Improvement the Hardness of Stainless Steel 321 by Magnetic Abrasive Finishing Process - Mousa, Shakir M. (Al-Nahrain Journal for Engineering Sciences, 2017)
Magnetic Abrasive Finishing (MAF) process which is a non-traditional polishing technique, is suitable for variety of engineering materials, producing high quality surfaces of parts. An experimental setup study is made to carry out MAF process to improve surface layer quality and hardness of stainless steel grade 321 plate. This study uses two different magnetic pole shapes such as conical magnetic pole without grooves and conical magnetic pole with six grooves. The finally results show that the conical magnetic pole with six grooves can create best surface layer quality and improve hardness in (MAF) process. The process parameters are the applied number of pitches between grooves, finishing time, cutting speed of magnetic pole, voltage, and volume of powder (dose). The magnetic abrasive powder consisted of silicon carbide SiC, particle size 300?m, SiC (65%), it is mixed with the ferromagnetic iron particles (iron powders), particle size 300?m, Fe (35%). Taguchi matrix L18 for five input parameters with mixed level design (2-3) levels was used for designing the experiments and optimal values evaluation for all parameters to improve the hardness. By using MINITAB software data was analyzed, the results indicate that empirical equation (mathematical predicted models) represents the relation of the input parameters with the change in micro Vickers Hardness. The most significant parameters on change in hardness are volume of powder (42.34%) and number of pitches between grooves (25.30%).